Mapping Glacier Structure in Inaccessible Areas From Turning Seismic Sources Into a Dense Seismic Array - Nanni, Ugo; Roux, Philippe; Gimbert, Florent (Geophysical research letters, 2024)
Understanding glaciers structural heterogeneity is crucial for assessing their fate. Yet, places where structure changes are strong, such as crevasses fields, are often inaccessible for direct instrumentation. To overcome this limitation, we introduce an innovative technique that transforms seismic sources, here generated by crevasses, into virtual receivers using source‐to‐receiver spatial reciprocity. We demonstrate that phase interference patterns between well‐localized seismic sources can be leveraged to retrieve phase velocity maps using Seismic Michelson Interferometry. The obtained phase velocity exhibits sensitivity to changes in glacier structure, offering insights into the origins of mechanical property changes, with spatial resolution surpassing traditional methods by a factor of five. In particular, we observe sharp variations in phase velocity related to strongly damaged subsurface areas indicating a complex 3‐D medium. Applying this method more systematically and in other contexts will enhance our understanding of the structure of glaciers and other seismogenic environments. Key Points We transform seismic sources from crevasses into virtual receivers using source‐to‐receiver spatial reciprocity We derive phase velocity maps in previously inaccessible areas with a resolution five times larger than traditional approaches We retrieve the influence of glacier geometry and structural heterogeneity on the glacier mechanical properties